2006
DOI: 10.1590/s1516-35982006000200003
|View full text |Cite
|
Sign up to set email alerts
|

Grazing management strategies for massaigrass-forage peanut pastures: 2. productivity, utilization and sward structure

Abstract: -This study was carried out to evaluate the productivity, utilization and sward structure of a mixed massaigrass (Panicum maximum x P. infestum, cv. Massai) and forage peanut (Arachis pintoi Ac 01) pasture, intermittently stocked at three daily herbage allowance levels (9.0, 14.5 and 18.4% of live weight). In each grazing cycle, dry matter (DM) accumulation rates, defoliation intensity (%), grazing depth (%) and grazed horizon (cm) were evaluated. The structure of massaigrass tussocks was characterized in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
4
5
1
1
Order By: Relevance
“…A. pintoi survives in well-drained areas, even though there is a severe leaf loss during the dry season, but resprouting is strong with the warmer temperatures of spring (Andrade et al, 2006). This work also found that weather conditions directly affected the production of this legume in the dry season of 2010.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…A. pintoi survives in well-drained areas, even though there is a severe leaf loss during the dry season, but resprouting is strong with the warmer temperatures of spring (Andrade et al, 2006). This work also found that weather conditions directly affected the production of this legume in the dry season of 2010.…”
Section: Resultssupporting
confidence: 54%
“…This is probably due to excessive shading during the growth period with maize. When assessing the dynamics and botanical composition of a Massai grass + Arachis pintoi pasture intercropping, Andrade et al (2006) also observed that the participation of Arachis increased throughout the experimental period, particularly in pastures with a lower and more open canopy. The authors concluded that Arachis can be successfully intercropped with Massai grass if the pasture height in the pre-grazing condition is kept below 60 cm to prevent excessive shading of legumes.…”
Section: Resultsmentioning
confidence: 87%
“…Amarillo (21.7 to 29.3 t/ha of DM), in Costa Rica, where annual rainfall is twice that recorded in Rio Branco-Acre, besides being better distributed along the year. Values of annual DM production in this study are also inferior to those reported by Andrade et al (2006a) for swards of massaigrass and forage peanut in Acre (20.4 to 29.2 t/ha of DM). This is probably due to the higher production potential of massaigrass in comparison with marandugrass, and also due to the soil waterlogging during part of the rainy season, which affected negatively the growth of marandugrass.…”
Section: Resultscontrasting
confidence: 99%
“…In the present study, grazed horizon was similar (mean of 17.1 cm) in the different treatments ( Figure 2E), an expected result in swards managed under different forage allowances, since higher swards are less intensively grazed and lower swards are more intensively grazed (Andrade et al, 2006a). Grazed horizon presented seasonal variation ( Figure 2F) similar to pre-grazing sward height (Andrade et al, 2012), with high correlation between the two variables (r = 0.96), a result similar to that reported by Brâncio et al (2003), evaluating three P. maximum cultivars and by Andrade et al (2006a) in a study with a mixed pasture of massaigrass and forage peanut. Grazed horizon was bigger during the January-March period (mean of 26 cm), as a result of plant lodging, decreasing to 14 cm in the AprilJune period, and to only 9 cm in the July-September period.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation